Valetudinarium in the Roman fortress of Novae - Press, Ludwika (Balcanica Posnaniensia. Acta et studia, 1990)
The article discusses the discovery and reconstruction of a military hospital (valetudinarium) in the Roman fortress of Novae. The problem is significant for studies on the organization of medical facilities in the Roman army. The aim of the work is to present the structure and function of this building. The author uses archaeological data from excavations. The most important results indicate that it is the first identified valetudinarium in Lower Moesia, dated to the early 2nd century AD. The building had a rectangular plan with an internal courtyard and a system of hospital rooms arranged around corridors. The conclusion confirms the high level of medical organization in the Roman army and the importance of Novae.